Glucocorticoid Therapy in ANCA Vasculitis: Using the Glucocorticoid Toxicity Index as an Outcome Measure. Issue 6 (24th June 2021) - Floyd, Lauren; Morris, Adam; Joshi, Miland; Dhaygude, Ajay
Abstract: Key Points: Glucocorticoid Toxicity Index provides a global quantifiable assessment tool to assess glucocorticoid associated morbidity. Cumulative doses of steroids in ANCA associated vasculitis leads to worse glucocorticoid related toxicity. Whilst glucocorticoids remain the mainstay of AAV treatment, the narrow therapeutic window supports the need for GC-sparing treatments. Background: ANCA-associated vasculitis (AAV) is an autoimmune disease. Induction remission and maintenance treatment typically includes high-dose, tapering glucocorticoids (GC), in addition to other immunosuppressive medication. The use of theGlucocorticoid Toxicity Index (GTI) provides a global, quantifiable assessment tool in which clinicians can assess GC-associated morbidity. Recent trials in AAV have exposed the need for systemic assessment of GC burden. In this small cohort study, we look to address these issues and the justification of newer GC sparing agents, such as C5a inhibitors. Methods: A retrospective cohort study of 43 patients with biopsy AAV was constructed from a single center between 2012–2016, and followed up for 48 months. The GTI table made up of adverse features was used to quantify patients' GC toxicity. Electronic patient records were reviewed and scores calculated according to published methods. GTI scores were compared with cumulative steroid doses at separate intervals and incidences of adverse features in relation to the treatment timeline. Results: The mean age was 65.9 (±11.06) years and treatment regimens consisted of glucocorticoids alongside cyclophosphamide or rituximab. Our results showed statistical significance in the association of cumulative GC doses and GTI scores ( P =0.008; 95% CI, 1.31 to 8.05). Adverse features relating to mood disturbance and GC-induced psychosis occurred early, in contrast to adrenal insufficiency, which typically presented later in the follow-up. Infection-related adverse events were consistent throughout. Conclusions: We demonstrated that higher cumulative doses of steroids in AAV lead to worse glucocorticoid-related toxicity. Using the GTI creates the potential to individualize and quantify the adverse effects patients experience as a result of GC treatment and permits more patient-centered management. Although glucocorticoids remain the main adjunctive immunosuppression of AAV treatment, the narrow therapeutic window supports the need for GC-sparing treatments.